Body Covers as Digital Display: A New Material for Expressions of Body & Self - Thieme, Anja; Steiner, Helene; Sweeney, David; Banks, Richard (Ubicomp/ISWC'16 Adjunct, 2016)
Within the domain of wearables, our paper explores opportunities for self-expression, learning about the body, and interactions with others that are enabled through the physical and interactive properties of a new kind of digital display. Recent advances in the manufacturing of thin, bendable electronics and a novel architecture for arranging pixels permit the fabrication of a ‘display material’ that challenges conventional perceptions of this medium. Envisioning digital displays as a material means that their design is no longer limited to rectangular screens, but can be scaled in size; cut, folded or molded; or combined with other materials and devices to create compelling interactions. In this paper, we explore some of this potential in the context of configuring body-worn items such as clothing. As a more concrete use example, we further present and discuss some initial ideas for aesthetic, expressive and functional configurations of body casts as a specific kind of body cover.